2021
DOI: 10.1002/pbc.28992
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous melanoma in children and adolescents: The EXPeRT/PARTNER diagnostic and therapeutic recommendations

Abstract: Cutaneous melanoma is rare in children and, like other very rare pediatric tumors, it suffers from a shortage of knowledge and clinical expertise. The clinical management of pediatric melanoma is often challenging. Its clinical and pathological diagnosis may be difficult, and there is no standard treatment. In the absence of specific treatment guidelines, young patients are generally treated following the same principle as for adults, but concern remains about their access to clinical trials and new drugs, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 84 publications
0
21
0
Order By: Relevance
“…Similar cooperative analyses have also been established for colorectal carcinoma and malignant melanoma [16,23]. These works have been the basis for establishing closer international collaboration with the funding of the European Commission as part of the ExPO-r-Net (European Expert Pediatric Oncology Reference Network for Diagnostics and Treatment) and partner projects [1,3,5,16,17,26,34,37]. By joining international groups into one registry, it becomes possible to gain further knowledge, especially for very rare tumors.…”
Section: Discussionmentioning
confidence: 75%
“…Similar cooperative analyses have also been established for colorectal carcinoma and malignant melanoma [16,23]. These works have been the basis for establishing closer international collaboration with the funding of the European Commission as part of the ExPO-r-Net (European Expert Pediatric Oncology Reference Network for Diagnostics and Treatment) and partner projects [1,3,5,16,17,26,34,37]. By joining international groups into one registry, it becomes possible to gain further knowledge, especially for very rare tumors.…”
Section: Discussionmentioning
confidence: 75%
“…Prior literature suggests that pediatric melanoma behaves distinctly from melanoma in adults, suggesting that a one‐size (or margin width) fits‐all approach may not be appropriate for all age groups 13,18,19 . Although it is difficult to perform randomized trials in the pediatric population, given the rarity of the disease as highlighted in the recent EXPeRT/PARTNER recommendations for cutaneous melanoma in children and adolescents, retrospective and database studies may shed light on the impact of excision margin width, specifically in the pediatric melanoma population 5,7,8 . Using a large national cohort of children with melanoma, we found that primary melanoma tumor resection with narrow margins (≤1 cm) in pediatric melanoma was associated with similar OS compared to wider (>1 cm) margins.…”
Section: Discussionmentioning
confidence: 91%
“…Surprisingly, our additional finding that there was no interaction between excision margin width and Breslow depth further suggests that the effect of excision margin width on OS does not differ based on Breslow depth. An adequately powered prospective trial to determine optimal surgical margins for children would be impractical due to the rarity of the disease, and some may argue lack equipoise given the data currently available in the adult population 5 . Instead, retrospective studies such as ours may help provide valuable information to guide clinicians who care for children with melanoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations